2020
DOI: 10.3390/foods9020151
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Nutrient Composition of Mealworms (Tenebrio Molitor) Fed on Fresh Plant Materials-Supplemented Diets

Abstract: Mealworms (Tenebrio molitor) have a great potential to serve as a sustainable food source for humans due to their favorable nutrient profile and low environmental impact. Feed formulation and optimization are important for mealworm production. The objective of this study was to evaluate the effects of fresh plant materials-supplemented diets on the growth performance and nutritional value of mealworms. Mealworm larvae were grown on wheat bran or wheat bran enriched with carrot, orange, or red cabbage for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 41 publications
(44 reference statements)
3
41
0
2
Order By: Relevance
“…Among various types of edible insects, the mealworm ( Tenebrio molitor L.) is one of the most popular species as a food and feed resource, and its extensive utilization has resulted in the advancement and establishment of commercial large-scale rearing systems [ 6 ]. Significant interest in mealworms has led to numerous studies on their growth and development [ 7 ], mass production systems [ 8 ], and nutrition value for use as feed [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of edible insects, the mealworm ( Tenebrio molitor L.) is one of the most popular species as a food and feed resource, and its extensive utilization has resulted in the advancement and establishment of commercial large-scale rearing systems [ 6 ]. Significant interest in mealworms has led to numerous studies on their growth and development [ 7 ], mass production systems [ 8 ], and nutrition value for use as feed [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diet affected the survival and development period of T. molitor; furthermore, feeding carrots increased the dry matter content and nitrogen efficiency, and decreased the development period. Contrarily, Liu et al [20] reported that wheat bran supplemented with approximately 30% fresh plant materials did not significantly affect mealworm survival, development, and proximate composition; however, its growth rate and final weight were improved. Lundy and Parrella [18] measured the biomass output and feed conversion ratio of A. domesticus reared on diets ranging from grain-based to highly cellulosic diets, and concluded that the nitrogen concentration, N-to-acid detergent fibre concentration ratio, and crude fat concentration explained most of the variabilities among feed treatments.…”
Section: Introductionmentioning
confidence: 99%
“…That the nutrient composition of mealworms can be influenced by fresh plant supplements in their diet during the growing phase of the insects was demonstrated by Changqi Liu and co-workers [ 36 ]. When mealworm larvae were reared on wheat bran enriched with carrot, orange, or red cabbage for four weeks, the larvae grew better and bigger, being 40–46% heavier than the controls that did not receive the food supplements.…”
Section: Resultsmentioning
confidence: 99%